2008
DOI: 10.1021/nl801038t
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Local Optical Response of Semiconducting Carbon Nanotubes to DNA-Wrapping

Abstract: We studied the local optical response of semiconducting single-walled carbon nanotubes to wrapping by DNA segments using high resolution tip-enhanced near-field microscopy. Photoluminescence (PL) near-field images of single nanotubes reveal large DNA-wrapping-induced red shifts of the exciton energy that are two times higher than indicated by spatially averaging confocal microscopy. Near-field PL spectra taken along nanotubes feature two distinct PL bands resulting from DNA-wrapped and unwrapped nanotube segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 38 publications
3
55
0
Order By: Relevance
“…Compared to the average PL energy of DNA-wrapped (9,1)-SWNTs on substrate of 1.332 eV, the localized PL observed in Figure 3d with energies down to 1.310 eV is exceptionally red-shifted. 9 This can account for the strong degree of localization in Figure 3a. To support our model of exciton diffusion and localization, we complemented our experiment with numerical simulations.…”
Section: Resultsmentioning
confidence: 84%
“…Compared to the average PL energy of DNA-wrapped (9,1)-SWNTs on substrate of 1.332 eV, the localized PL observed in Figure 3d with energies down to 1.310 eV is exceptionally red-shifted. 9 This can account for the strong degree of localization in Figure 3a. To support our model of exciton diffusion and localization, we complemented our experiment with numerical simulations.…”
Section: Resultsmentioning
confidence: 84%
“…The main challenge for TERS is the development of new and robust instrumentation for achieving a ready-to-use system. TERS in sp 2 nanocarbons started focusing on experimental work [23][24][25][26][27][28][29][30], but recently theoretical studies are appearing in both one-dimensional (SWNTs) [116] and two-dimensional (graphene) [117] materials, thus guiding the way for future developments.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their low dimensionality and huge optical response, carbons nanotubes started to be widely used as a prototype for the development of TERS. Some results achieved in carbon nanotubes were nanoscale vibrational analysis [25], nanoscale optical imaging of excitons [26], TERS polarization measurements [27], imaging of nanotube chirality changes [28], spectral determination of singlecharged defects [29], and local optical response of semiconducting nanotubes to DNA wrapping [30], among others. A comprehensible review for TERS in carbon nanotubes can be found in [31].…”
Section: Historical Development Of Raman Spectroscopy Applied To Sp 2mentioning
confidence: 99%
“…The two dashed arrows mark beginning and end of the (9,1) nanotube determined from the simultaneously detected G-band Raman signal (not shown Figure 2, respectively, such shifts can also be explained by nonuniform DNA-wrapping as found for single DNAwrapped nanotubes. 27 Emission from the (9,1) nanotube (Figure 2a) occurs in four bright segments, while emission from the (6,5) nanotube (Figure 2b) is more extended for about 1 µm. This can also be seen in the intensity profiles shown in Figure 2e taken along the two dashed lines in Figure 2a,b.…”
mentioning
confidence: 99%